Analisis Struktur Geologi Sistem Panas Bumi Menggunakan Metode Gaya Berat di Daerah Danau Maninjau Sumatera Barat - putra, yoga satria (Himpunan Ahli Geofisika Indonesia (HAGI), 2023)
A geothermal system is generally associated with faults in geological structures. Therefore, identifying faults in the geothermal system is a critical study. This study aims to identify the presence of faults and to model the geological structure of a geothermal system in the Maninjau Lake area using the gravity method. Indication of the faults is determined based on gradient analysis of the first horizontal derivative (FHD) and second vertical derivative (SVD). While the subsurface structure modelling is done using forward modelling. The data used in this study is gravity disturbance data obtained on the GGMplus page. Based on the study's results, the geothermal system that developed in the Maninjau Lake area was the remnants of magma from the eruption of the Maninjau volcano. This residual magma becomes a heat source that controls the geothermal system in this area, as evidenced by the presence of volcanic rock formations in the form of basaltic andesite, pumice lapilli and basalt rock in the study area. Based on the analysis, the geological structure of the geothermal system in this area is composed of reservoir rock and cap rock. Based on the results of 2D modelling of subsurface geology, the reservoir rock consists of sandstone with a rock density of 2.76 gr/cm3 at a depth of up to 600 m. This study did not detect cover rock because it is located at a very shallow depth. The faults around the hot springs of Lake Maninjau were identified using derivative analysis. This fault can be used as a hydrothermal route for geothermal manifestations in the Maninjau Lake area. Geologically, the geothermal system in the Lake Maninjau area is included in the volcano-tectonic geothermal system.